On a possibility of nondisturbing monitoring of electron-radiation absorbed dose in radiation-technological processes - Karasyov, S.P.; Nikiforov, V.I.; Pomatsalyuk, R.I.; Tenishev, A.Eh.; Uvarov, V.L.; Shevchenko, V.A.; Shlyakhov, I.N.; Malets, E.B. (Вопросы атомной науки и техники, 2006)
Great deals of present-day radiation technologies that use electron accelerators involve the procedure of transporting the products under treatment across the irradiation zone normally to the beam scanning plane. The main controlled characteristic of the process is the electron radiation dose absorbed in the object under treatment. The present paper offers the method of nonperturbing real-time dose and electron energy monitoring. The method is based on the analysis of distribution of currents from the plates of a sectionalized beam charge absorber. The absorber is placed behind the conveyor and is periodically shut off from the beam by the object under irradiation. The method was preliminarily analyzed through computer simulation.